PERMASALAHAN ORANG TUA YANG MEMILIKI REMAJA AUTISME PADA MASA PUBERTAS (Studi Kasus terhadap Orang Tua di Yayasan Wacana Asih Tarandam Padang) - -, Rahayu - (Bimbingan dan Konseling, 2014)
This research is motivated by parents who have teenagers with autism at puberty based study of parents who have teenagers with autism experience more problems than other parents, especially during puberty. This study aimed to look at the physical and psychological problems of parents who have teenagers with autism at puberty, the focus of this study was to describe the physical and psychological problems of parents who have teenagers with autism at puberty. This research was conducted with a qualitative descriptive approach that describes symptoms, facts and reality in the field what it is about the physical and psychological problems of parents who have teenagers with autism at puberty. Instruments that researchers use in this study were interviews, observations, techniques used in processing the data through data reduction, presentation and conclusion.The results of studies that have analyzed revealed that the health condition of the elderly declined, as parents headaches , high blood pressure, decreased appetite , fatigue , lethargy and fatigue , concentration and disturbed parents work, the incidence of misunderstanding between husband and wife, was not comfortable with the condition of autism teenagers at the time had a problem, and the familys economic decline. Based on the research results to parents and stakeholders to be able to overcome the obstacles encountered by parents who have children with autism in their teens so that these obstacles can be overcome with the optimal .